Drawing, Painting and Digital Painting Series "Sensoji Temple 2018" - ฉายะเจริญ สุริยะ (Siam Communication Review, 2019)
This article is intended to describe the creative process of drawing, painting and digital painting series "Sensoji Temple 2018". The author was inspired by his trip to Tokyo, Japan. And analysis is a concept and lead to a systematic process. Successful creative works can be divided into four categories: drawing, drawing watercolor, acrylic and digital painting. Each type has its own advantages and disadvantages that are identical and different. But the expression of the meaning of the work still expresses clearly that communication can be concluded under the concept. It represents the identity created by the integration between the cultural and spiritual pathways of the spiritual realm and the context of Sensoji Temple’s modern world travel.